Avoiding the sintering of coal fired shallow fluidized beds - Afilaka, Daniel T. (2016)
Fluidised bed combustion (FBC) has been identified as one of the best technologies available for lump coal combustion. A major drawback during prolonged operation of FBC systems particularly bubbling fluidised bed (BFB) systems is sintering and agglomerate formation of bed material that affects performance efficiency and reliability in industrial applications as exemplified at Associated British Sugar (AB Sugar). The mechanisms responsible for sintering and agglomerate formation in this type of system need to be understood, to promote continual use of this technology for efficient coal utilisation. The first set of investigations focused on agglomeration properties of bed material (Garside 14/25 sand) used in Industrial FBC at AB Sugar. Bed material was calcinated between 800 and 1200°C in a high temperature furnace in the absence and presence of coal (three types of bituminous coals) or coal ash. Results showed sintering and agglomerate formation of bed material can occur in the absence of coal or coal ash at a calcination temperature near 1200°C. Addition of coal or coal ash further promotes sintering and agglomerate formation at 1000°C. Combustion stages appears to influence surface morphology, chemistry and mechanisms of agglomerated bed material based on similarities observed in the agglomerated bed material formed from calcination of Garside 14/25 sand bed material mixed with coal, and those formed in industrial scale FBC during combustion of lump coal.